2020
DOI: 10.1021/acsanm.0c00223
|View full text |Cite
|
Sign up to set email alerts
|

Low Melting-Point Alloy–Boron Nitride Nanosheet Composites for Thermal Management

Abstract: The interface thermal resistance (ITR) of thermal interface materials is discussed in terms of electronic unit heat dissipation. To reduce the ITR of heat-conducting silicone grease (HCSG), low melting-point alloys (LMPAs) are introduced using boron nitride nanosheets (BNNS) via a simple route for thermal management. The results reveal that LMPAs uniformly compound and coat BNNS at the nanometer level. The BNNS narrows the LMPAs’ melting range. After reaching the melting point, the composite powder shows a deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Despite the improved properties, both the density of Ga-based LMs (EGaIn: 6.25 g cm −3 ; galinstan: 6.44 g cm −3 ) and typically high loading (⩾85 wt%, or ⩾50 vol%) required to achieve the desired functional properties contribute to the high density of LM embedded composites, which can be problematic for largearea and weight-sensitive applications.Recently, researchers have shown that the properties of Gabased LMs can be enhanced through the addition of solid particles. Several LM mixtures have been studied to improve the thermo-mechanical properties [10,11,[40][41][42][43][44][45][46][47][48][49] , rheology and consistency, [50][51][52][53][54][55][56][57][58] and density [58,59] of LM. This has resulted in LM mixtures with high thermal conductivity >100 W m −1 K −1 , a fourfold increase as compared to pure LM, [43,44] LM pastes that can be easily spread on a surface, [40] and LM mixtures that can float on water.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the improved properties, both the density of Ga-based LMs (EGaIn: 6.25 g cm −3 ; galinstan: 6.44 g cm −3 ) and typically high loading (⩾85 wt%, or ⩾50 vol%) required to achieve the desired functional properties contribute to the high density of LM embedded composites, which can be problematic for largearea and weight-sensitive applications.Recently, researchers have shown that the properties of Gabased LMs can be enhanced through the addition of solid particles. Several LM mixtures have been studied to improve the thermo-mechanical properties [10,11,[40][41][42][43][44][45][46][47][48][49] , rheology and consistency, [50][51][52][53][54][55][56][57][58] and density [58,59] of LM. This has resulted in LM mixtures with high thermal conductivity >100 W m −1 K −1 , a fourfold increase as compared to pure LM, [43,44] LM pastes that can be easily spread on a surface, [40] and LM mixtures that can float on water.…”
mentioning
confidence: 99%
“…Recently, researchers have shown that the properties of Gabased LMs can be enhanced through the addition of solid particles. Several LM mixtures have been studied to improve the thermo-mechanical properties [10,11,[40][41][42][43][44][45][46][47][48][49] , rheology and consistency, [50][51][52][53][54][55][56][57][58] and density [58,59] of LM. This has resulted in LM mixtures with high thermal conductivity >100 W m −1 K −1 , a fourfold increase as compared to pure LM, [43,44] LM pastes that can be easily spread on a surface, [40] and LM mixtures that can float on water.…”
mentioning
confidence: 99%
“…LM‐BN composite exhibits the lowest thermal and electrical conductivities among all the samples we fabricated due to the mismatch of electrons and phonons between electrically insulated BN and LM. [ 55 ] Therefore, in this work, hybrid fillers of 2D materials coated with metal (e.g. graphene nanoplates coated with nickel) exhibit both the above advantages.…”
Section: Resultsmentioning
confidence: 99%
“…Typical TIMs are mainly made up with an organic matrix (including thermal greases, 13,14 gels, 15–18 epoxy, 19 silicone based elastomer composites 20 ) and thermally conductive fillers ( e.g. , metals, oxides, carbon materials, metal nitrides, low melting alloys) 21–23 for their easy processability and low cost.…”
Section: Introductionmentioning
confidence: 99%